STRATEGIES TO REDUCE THE PREVALENCE OF ANEMIA IN PREGNANT WOMEN A QUALITATIVE STUDY - Ariska Fauzianty (Jurnal Rumpun Ilmu Kesehatan, 2022)
Anemia during pregnancy is still a global problem. The government synergizes with health workers to reduce the prevalence of anemia, one of which is by administering iron supplements. However, this alternative has not been able to reduce the incidence of anemia in Indonesia. Therefore, the aim of this study was to determine strategies to reduce the incidence of anemia in pregnant women. Qualitative research with a single holistic case study approach. Research informants were heads of puskesmas, midwives, nutritionists, ATLM, doctors, and anemic pregnant women. Data collection for 1 month. Data analysis using Miles and Huberman models. The data collection instruments were interview guides, study documentation, observations, logbooks and field notes. The results of this study, there are 4 themes namely: 1) increasing the competence of human resources; 2) providing more comprehensive health education and simpler word choices; 3) Educational media innovation by utilizing online platforms; and 4) husband and family support. Therefore, increasing human resources can be through training and technical guidance on the management of anemia during pregnancy and anemia hematology examination, utilizing social media platforms such as Instagram, TikTok, Youtube and Whatsapp. increased blood especially drinks that can block the absorption of iron. Also, husbands encourage and remind pregnant women to regularly consume iron tablets every day.